Improved outcome with pulses of vincristine and corticosteroids in continuation therapy of children with average risk acute lymphoblastic leukemia (ALL) and lymphoblastic non-Hodgkin lymphoma (NHL): report of the EORTC randomized phase 3 trial 58951 - De Moerloose, Barbara (American Society of Hematology, 2010)
The European Organisation for Research and Treatment of Cancer 58951 trial for children with acute lymphoblastic leukemia (ALL) or non-Hodgkin lymphoma (NHL) addressed 3 randomized questions, including the evaluation of dexamethasone (DEX) versus prednisolone (PRED) in induction and, for average-risk patients, the evaluation of vincristine and corticosteroid pulses during continuation therapy. The corticosteroid used in the pulses was that assigned at induction. Overall, 411 patients were randomly assigned: 202 initially randomly assigned to PRED (60 mg/m(2)/d), 201 to DEX (6 mg/m(2)/d), and 8 nonrandomly assigned to PRED. At a median follow-up of 6.3 years, there were 19 versus 34 events for pulses versus no pulses; 6-year disease-free survival (DFS) rate was 90.6% (standard error [SE], 2.1%) and 82.8% (SE, 2.8%), respectively (hazard ratio [HR] = 0.54; 95% confidence interval, 0.31-0.94; P = .027). The effect of pulses was similar in the PRED (HR = 0.56) and DEX groups (HR = 0.59) but more pronounced in girls (HR = 0.24) than in boys (HR = 0.71). Grade 3 to 4 hepatic toxicity was 30% versus 40% in pulses versus no pulses group and grade 2 to 3 osteonecrosis was 4.4% versus 2%. For average-risk patients treated according to Berlin-Frankfurt-Muenster–based protocols, pulses should become a standard component of therapy. This trial was registered at www.clinicaltrials.gov as #NCT00003728.